Maimonides and his Impact on Jewish Religious Discourse through his Book "Guide for the Perplexed": An Analytical Study - Al-Gananeem, Eman Ali Mohammed; Al-Momani, Mohammed Khaled Mostafa (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: This study aims to shed light on the most important philosophers of Judaism, and the extent of the impact of Islamic civilization on the thought of Jewish religious discourse among them, by standing on the impact of the philosopher Maimonides on Jewish beliefs. The study delves into the topics of the prophethood, divine auditions, and their impact on Jewish theology concerning natural phenomena. Methods: The study involves tracing the life of Maimonides, who lived during the medieval period, and examining his book "Guide for the Perplexed." It serves as evidence of his approach that reconciles between scripture and reason in matters related to monotheism, prophethood, divine auditions, and natural phenomena. Results: The study found that Maimonides was a Jewish philosopher who did not convert to Islam, but he was influenced by Islamic civilization, evident in his book. In the book, he reaffirmed the belief of monotheism, distancing God from corporeality and similarity. He also emphasized the status and role of prophets in the Torah. Moreover, Maimonides believed that all natural phenomena serve a purpose instilled by its Creator to achieve certain ends, whether humans comprehend them or not. Conclusion: Maimonides’ work contributed to the renewal of Jewish religious thought through his ideas presented in the book "Guide for the Perplexed." The study recommends further exploration of specific topics and analyses from his book, such as issues of preexistence and creation of the world, divine attributes, and other matters.